Pengaruh Penganggaran Berbasis Kinerja, Kejelasan Sasaran Anggaran Dan Partisipasi Anggaran Terhadap Akuntabilitas Kinerja Aparat Pemerintah Daerah (Studi Kasus Pada Dinas Pendapatan, Pengelolaan Keuangan dan Aset Daerah Kabupaten Sragen) - Rohmawati, Intan; , Drs. Suyatmin Waskito Adi, M.Si (2016)
The purpose of this study was to analyze the influence of Performance- Based Budgeting, Goal Clarity budget, the Budget Participation accountability Performance Against Local Government Officials at the Dinas Pendapatan, Pengelolaan Keuangan dan Aset Daerah Kabupaten Sragen. This study uses population of the entire apparatus DPPKAD Sragen which numbered 40 people with sampling Convenience sampling technique. Number of questionnaires distributed by 40 and returning as many as 33. The sample in this study were processed using 33 sample and processed using multiple linear regression analysis in order to determine the effect of performance-based budgeting, Kejalasan Target Budget and Budget Participation Of Local Government Performance Accountability , The results showed simultaneous variable performance-based budgeting, Goal Clarity Budget and Budget Participation influence on Government Performance Accountability. The partial results of the study as follows: (1) performance budgeting is partially an effect on performance accountability at the level of significance 0.019 <α = 0.05 so the first hypothesis is accepted. (2) The budget goal clarity partial effect on accountability for performance at a significance level of 0.027 <α = 0.05 seehingga second hypothesis is accepted. (3) participation in partial budget does not affect the performance accountability at the level of significance 0.044 <α = 0.05 so 3 hypothesis is accepted.